(3GdGJUGdGJ GdTNUjI GddGSdcjI (B:s (3eSJbHd GdeMGOKI (B/s - (3TfGjOQeGf, Qhfs; (3SdWGf(B;Schneidemans ((3GdQjGV (B:s (3GdfTQ GdYdej h GdeWGHY ,s, 1997)
(3JfHY GgejI gPG GdcJGH ef NWhQI GdehVhY GdPj jJfGhdg h MOGKJg h bQGAJg SJDOj Gdi ehGcHI h eYQaI GaVd ddJbOe GdeJSGQY aj eLGd GdGJUGdGJ GdTNUjI GddGSdcjIs
Keywords: (3GdGJUGdGJ GdSdcjI h GddGSdcjIs; (3SdWGf(B, (3CHhHcQs